Relationships Between Maternal Antenatal Attachment, Toddler Temperament, Maternal Sensitivity And Toddler Attachment Security In Yogyakarta, Indonesia - Muti'ah, Titik (2009)

(untitled)
The mother-toddler relationship as an important aspect for further child’s development of secure attachment has not been detail studied in Indonesia. This study has been conducted to investigate the relationships between maternal antenatal attachment, toddler temperament, maternal sensitivity and toddler security attachment in Yogyakarta, Indonesia. Mixed methods approach (quantitative, qualitative) and design (cross-sectional and retrospective methods) was adopted in this study to examine the relationship among variables. Eighty-four pairs of mothers and toddler dyads participated as the respondents in this study. Data were collected using combination of observation, interviews, self-reports and questionnaire. Observation method was applied to obtain data on toddler attachment security and maternal sensitivity using TAS-45 (Toddler Attachment Sort) and MBQS (Maternal Behavior Q-Sort). Interview method was applied to measure the maternal antenatal attachment to the unborn baby using the modified of Condon’s MAAS (Maternal Antenatal Attachment Scale). The toddler temperament and maternal antenatal attachment of childhood were determined from the respondent’s score through the Toddler Temperament Scale (TTS) and Perception of Adult Attachment Questionnaire (PAAQ). Eleven mothers have been selected for the in-depthinterview to understand further the phenomena and enhance the interpretation of the quantitative finding. The results obtained from the quantitative approach showed that child sex, family income, mother education, maternal antenatal attachment (28.7%), activity dimension of toddler temperament (16.1%) and maternal sensitivity (46%) have contributed significantly (62.2%) to the variance in the toddler attachment security. Other temperament dimensions (regularity, approach, adaptability, mood, intensity, distractibility, persistence, threshold, reactivity and self-regulation) did not show any significant relationships with other independent and dependent variables. However, the qualitative findings revealed a pattern of relationship between maternal antenatal attachment developed during her childhood experiences, maternal antenatal contextual factors as well as toddler temperament and toddler attachment security. The toddler attachment security in Indonesia showed the same pattern as the Asian proportion of attachment style. This research study has supported the applicability of attachment theory in maternal and toddlers secure attachment in Indonesian culture. The quality of maternal attachment and behaviors as primary caregiver must be provided from the time of conception (antenatal period) and maintained during the toddler development. The maternal antenatal attachment and toddler characteristic had profound and durable effects on the toddler attachment security and mental health. The result of this study adds to our understanding of the mother’s role in promoting and maintaining of healthy and secure child attachment.